The Relationship between Ghrelin and Copeptin Levels, and Anxiety and Depression Levels in Suicide Attempts - Atescelik, Metin; Yilmaz, Mustafa; Korkmaz, Sevda; Goktekin, Mehmet Cagri; Gurger, Mehtap; Ilhan, Nevin (Korean Coll Neuropsychopharmacology, 2017)
Objective: It was aimed to detect acylated ghrelin (AG), unacylated ghrelin (UG) and copeptin levels in patients with suicide attempts and to determine if these biomarkers are risk factors for suicide attempts. Methods: Serum copeptin, AG and GU levels were screened in 128 patients who were admitted to emergency department with suicide attempts and 59 healthy controls. Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) were applied simulta neously, and the data were compared statistically. Results: AG, UG and copeptin levels were higher in the patient group compared with the healthy control group. BAI scores of patients were found to be positively correlated with BDI scores. While there was a significant difference (p=0.0064) between psychiatric and non psychiatric patients with suicide attempts in terms of BAI scores, there were no differences in BDI scores and levels of biomarkers. We found significantly increased BDI and BAI scores and increased levels of AG, UG and copeptin in psychiatric and non psychiatric patients compared with healthy individuals. The specificities yielded by receiver operating char acteristic curve analysis in patients with suicide attempts were as follows: 91.53% for AG, 72.88% for UG and 94.92% for copeptin. Conclusion: Serum levels of AG, UG and copeptin increase with increasing anxiety and depression in patients with suicide attempts. Increased levels of AG, UG and copeptin could be considered a risk factor for suicide attempts.
Keywords: Acylated ghrelin; Beck Anxiety Inventory; Beck Depression Inventory; Copeptins; Suicide; Unacylated ghrelin